Effects of Yin and Yang supplement on reproductive performance, antioxidant and immunity of dairy goats - Kang Wang; Zhi Yang; Fumei Yang; Guanzong Li; Yulin Sun; Gang Duan; Jun He; Wang Sun; Ke Zhou; Zhihao Xiong; Feiyan Dai (Animal Biotechnology)
This study aims to explore the effects of Yin and Yang Double Supplement Compound Chinese Medicine Preparations (YYSBFF) on the reproductive performance, antioxidant levels, and immunity of dairy goats. For the experiment, 36 Alps milk goats were selected and randomly divided into an experimental group and a control group, with 18 goats in each group. The ewes in the experimental group were fed with YYSBFF for 14 d prior to breeding and farrowing. The results of the experiment showed that the estrus rate, embryo acceptance rate, and lamb birth weight in the experimental group were higher than those in the control group, and the weak lamb rate was significantly lower. Moreover, the experimental group exhibited higher levels of reproductive hormones (FSH, LH), antioxidant factors (T-SOD, GSH-Px, MDA), and immunoglobulins (IgA, IgM, IgG) compared to the control group. There were no significant differences in liver and kidney function indicators (ALT, AST, TP, ALB, CREA, UREA) between the experimental and control groups (p > .05). These findings indicate that YYSBFF can enhance the reproductive performance of dairy goats by regulating the level of sex hormones, while also improving the body’s antioxidant and immune abilities.